The effect of recycled – high density polyethylene (hdpe) mixing ratio on the tensile strength of high density polyethylene (hdpe) polymer - Siti Amni Husna , Roslan (2013)
High Density Polyethylene (HDPE) polymer is widely being used nowadays. The advantages possessed by this polymer make it more preferable than metals. Lightweight, ease of manufacture, stronger and tough are HDPE specialties that make it as the top choice by manufacturers. However, the main disadvantages about this material is that their decaying consumes much time and this effects the environment as this material will dispose as wastes if they could not longer being used. Also, cause loss to certain companies. Therefore, ways to overcome this problem must be found, which is by recycling process. In recycling HDPE polymer, there is one method that mostly been used which is by mixing the recycled HDPE with pure HDPE with certain percentage of both materials. In this project, the pure HDPE were mixed with recycled HDPE according to determined percentages. The samples produced then will undergo tensile test in order to determine the percentage which posses the optimum tensile strength. In the end of experiment, it showed that the mixture with 90% of pure HDPE with 10% recycled HDPE is the best percentage compared to others. This experiment was conducted by following ASTM D638.